Assessing future sponsors’ perceived value, attitude and willingness to sponsor trust schools program / Zaitun Udari, Nurfatin Ramlan and Muhammad Amir Amirul Mohamad - Udari, Zaitun; Ramlan, Nurfatin; Mohamad, Muhammad Amir Amirul (Arshad Ayub Graduate Business School, 2018)
Sponsorship is an important marketing tool in attracting parties to participate and provide support or assistance either in terms of finance, expertise, knowledge, or services in any event, project or program. In the context of the education industry in transforming the Malaysian education system through a Public-Private Partnership, the involvement of private and public sectors from various backgrounds to participate in a program called Trust Schools Program, an initiative between the Ministry of Education and Yayasan AMIR is the most critical. The objective of this research was to assess the influence of the future sponsors’ perceived value on the attitude and impact towards the willingness of the future sponsors of the Trust Schools Program. The four dimensions of perceived value namely functional, price, emotional and social were examined. A survey questionnaire approach was used to collect primary data from various companies. In additional an interview session with the Head of Program Management of Yayasan AMIR, a non-profit organisation formed by Khazanah Nasional Berhad was carried out to understand the current situational of Yayasan AMIR in managing the Trust Schools Program. Yayasan AMIR is the only private sector which had been given the mandate by the Ministry of Education to be involved in the transformation of the Malaysian education system. Though the Public-Private Partnership, Yayasan AMIR is permitted to invite other private sectors in any industrial background, individuals or alumni to sponsor this program. In order to have more private sectors participating in the Program, it is important to assess the attitude of the future sponsors which will impact their willingness to sponsor the Trust Schools Program based on the perceived value. Findings from the regression analysis showed that the future sponsors’ perceived value has a significant influence on the attitude towards the Trust Schools Program. It also showed that attitude has a positive impact on the willingness to sponsor the program. The key strategies for Yayasan AMIR to attract future sponsors were on communication and promotion strategies.